2013
DOI: 10.1371/journal.pone.0078721
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Ambient Odor on the Affective Appraisal of a Desktop Virtual Environment with Signs of Disorder

Abstract: BackgroundDesktop virtual environments (VEs) are increasingly deployed to study the effects of environmental qualities and interventions on human behavior and safety related concerns in built environments. For these applications it is essential that users appraise the affective qualities of the VE similar to those of its real world counterpart. Previous studies have shown that factors like simulated lighting, sound and dynamic elements all contribute to the affective appraisal of a desktop VE. Since ambient od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…That is, the highest store ratings were documented when the non-Christmas music was presented in the absence of any specific ambient scent. At the same time, however, it is worth bearing in mind here, given that Spangenberg et al (2005) only presented a series of pictures to the participants, other findings suggesting that scents do not have quite the same effect in virtual reality environments (Toet et al, 2013; see also Jiang et al, 2016).…”
Section: Smell In the Multisensory Built Environmentmentioning
confidence: 89%
See 1 more Smart Citation
“…That is, the highest store ratings were documented when the non-Christmas music was presented in the absence of any specific ambient scent. At the same time, however, it is worth bearing in mind here, given that Spangenberg et al (2005) only presented a series of pictures to the participants, other findings suggesting that scents do not have quite the same effect in virtual reality environments (Toet et al, 2013; see also Jiang et al, 2016).…”
Section: Smell In the Multisensory Built Environmentmentioning
confidence: 89%
“…As well as positively influencing our mood and emotion, it has been suggested that certain semantically meaningful scents are also capable of priming specific behaviors (e.g., Baron, 1990). So, for example, according to the results of a couple of published studies, people engage in significantly more cleaning, and are more likely to pick up rubbish, with a citrus cleaning scent in the air (Holland et al, 2005;De Lange et al, 2012; though see also Toet et al, 2013, for evidence suggesting that scents may have somewhat different effects in virtual environments). Meanwhile, other researchers have reported that the presence of 'clean' ambient scents (a spray of citrus-scented Windex) can also promote reciprocity (in a one-shot anonymous trust game) and charitable behavior (e.g., as assessed by the intention to volunteer; Liljenquist et al, 2010).…”
Section: Home and Office Smellsmentioning
confidence: 99%
“…To improve the immersive nature of the scenario being practiced, realism is improved by mimicry of the sights, sounds and tactile sensations participants might experience in a real-world scenario, and scenarios are designed to be emotionally realistic. Smell is rarely used during medical simulations, though it has the potential to alter the behaviour of participants,12 16 to further improve simulator validity,1 3 13 to assist in biographical memory formation9 17 18 and to desensitise trainees to strong malodours 7 8 19. We carried out a systematic review of literature relating to the use of smell in medical simulation training.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chen (2006): "scents are extremely evocative in the virtual world, they can shift attention, add novelty, enhance mental state and add presence" (p. 580; see also Gallace et al, 2012). That said, one of the key findings from the laboratorybased scent-enabled VR research that has been published to date has been that while unpleasant scents tend to increase immersion, positive and neutral scents often show little effect (e.g., Baus & Bouchard, 2017;Ghinea & Ademoye, 2012;Ischer et al, 2014; though see also Toet et al, 2013). Indeed, according to the title of a 2019 paper by Baus et al: "Exposure to a pleasant odour may increase the sense of reality, but not the sense of presence or realism."…”
Section: Scent-enabled Virtual Realitymentioning
confidence: 99%